DOK7 congenital myasthenic syndrome in childhood: Early diagnostic clues in 23 children - Klein, A; Pitt, M; McHugh, J; Niks, E; Sewry, C; Phadke, R; Feng, L; Manzur, A; Tirupathi, S; DeVile, C; Jayawant, S; Finlayson, S; et al. (2013)
Mutations in DOK7 are a common cause of congenital myasthenia. Treatment with ephedrine or salbutamol is effective, but diagnosis is often delayed. The aim of our study was to find early clues to the diagnosis of DOK7 congenital myasthenic syndrome. We included 23 children of 20 families. Onset of symptoms ranged from birth to age 3. years. 13 presented at birth with feeding difficulties, 11 with stridor (documented vocal cord palsy in 7), 3/11 with hypotonia/poor head control. Weakness was more pronounced proximally in all, axial in early presenting infants. Muscle biopsy showed non-specific features in 15/16, type 1 fibre predominance in 14/16, areas devoid of oxidative enzyme activity in 7/16. Muscle imaging was normal in 8/10, 2/10 showed mild non-specific changes. A diagnostic clue suggesting CMS rather than myopathy was the discrepancy between muscle imaging or histology findings compared with the degree of weakness. Repetitive nerve stimulation and stimulation single fibre electromyography were pathological in 9/17 and 13/14, respectively. In conclusion, stridor and feeding difficulties at birth or progressive weakness despite normal milestones in infancy point to the diagnosis and should lead to neurophysiological and genetic investigation. Fatigability can be absent or easily missed in the first years of life. © 2013 Elsevier B.V.